In vitro propagation of liquorice (Glycyrrhiza glabra L.) through multiple shoot formation - KUKREJA, ARUN KUMAR (Journal of Spices and Aromatic Crops, 1998)
In vitro plant regeneration of liquorice (Glycyrrhiza glabra) through, multiple shoot formation from nodal explants is reported. Addition of kinetin (0.05 mgI-’) and indole-3-acetic acid (1.0 mgI-’) to Nitsch medium resulted in rapid elongation of axillary buds. Proliferation of multiple shoots was more effective in Murashige and Skoog medium containing benzylaminopurine (2 mgI-’) and indole -3-acetic acid (1 mgl-1). In vitro regenerated shoots were rooted on Murashige and Skoog medium supplemented with 1 mg-1 indole-3-acetic acid and after acclamatization in the glasshouse were transferred to field with 95% survival.